Impact of Standard Guidelines on Nurses Knowledge and Practices Regarding the Prevention of Neonatal Sepsis at Public Hospital, Pakistan - Tahmina Bano, Hajra Sarwar, Kousar Perveen, Sadia Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Sepsis is one of the most frequently occurring complications that affect newborn infants. For pediatric age group, it serves as a prime base of mortality and morbidity. Objectives of this study are to evaluate the nurses’ knowledge and practices regarding the neonatal sepsis and to evaluate the impact of standard guidelines intervention program on nurses’ knowledge and practices regarding the prevention of neonatal sepsis. Methodology: This educational base randomized control trial was the knowledge and practices of the nurses were assessed using questionnaires and checklists distributed among the control group and the intervention group which was made to attend the training sessions. Mean scores of pre- and post-intervention and pre- and post-control groups were analyzed and compared statistically. Results: Post- intervention category showed the highest mean score of 11.38±2.26 as compared to other three categories. A significant difference (p <0.0001) was observed between the mean scores of pre and post intervention knowledge and practices scores while an insignificant differences as p=0.133 and p=0.111 were observed in mean scores of pre and post control groups of knowledge and practices respectively. Conclusion: The training session based on the standard guidelines to prevent neonatal sepsis was proved to be an effective intervention to enhance the knowledge of the nurses and their compliance with universal precautions.